Study of Urinary Excretion and Renal Clearance of Pioglitazone in Male Volunteers - Alim, Muhammad; Nawaz, Rakshanda; Rafique Asi, Muhammad; Shahid, Muhammad; Z. Iqbql, Shahzad; Abbas, Mateen (Asian Journal of Chemistry, 2010)
The urinary excretion and renal clearance of pioglitazone was investigated in 24 healthy male volunteers after oral administration of a single dose of 30 mg pioglitazone. Concentration of pioglitazone in plasma and urine was determined by high performance liquid chromatography (HPLC) and the concentration of creatinine by chemistry analyzer. In male volunteers the plasma concentration of pioglitazone was 0.576 μg/mL while the concentration of pioglitazone in urine was 0.277 μg/mL. Rate of urine flow (diuresis) recorded was 0.016 mL/min/kg. The renal clearance values of pioglitazone and endogenous creatinine were 0.012 and 0.672 mL/min/Kg, respectively. The ratio between the clearance of pioglitazone with the clearance of endogenous creatinine was 0.021. In urine of male volunteers, maximum concentration of pioglitazone excreted after 6 h was 0.463 μg/mL and cumulative amount of pioglitazone excreted was 150.77 μg.